EVALUASI DAN REMIDIASI DALAM PEMBELAJARAN BAHASA DAN SASTRA MULTILITERASI - Fadli, Rusli Ilham (Discovery, 2018)
ABSTRAKMultiliteration is currently a learning method that has been developed by teachers, whopreviously used literacy that only read and write less widely, currently multiliteration of students candevelop ways of reading and using various internet media and free media. Multiliteration remains to readand write. In reading students must have a septetap concept to read and write. In reading students musthave a septetap concept to read and write. In reading students must have criteria such as characters, taste,creativity, and desire, which allows each reader.Indonesian language learning has a very important role not only for communication and alsofor the benefit of mastering science. According to Ghazali (2010: 168) language learning is "a processthat runs linearly, which starts with English (listening and speaking) and then switches to writtenlanguage (reading and writing). So, nothing is interconnected and cannot be used in the learning process.However, reading and writing are very important, this is caused by reading for tools for things that canincrease knowledge and the development of messages in young reading material can be written in writing,namely writing. Even so, reading and writing books are easy to do and learn through the right learningprocess. The ability to read and the ability to write relationships that cannot be ignored.Based on the photoshoot about learning to read and write above the Target. The evaluationresults of Bloom's Taxonomy include cognitive, affective, psychomotor domains. In the third 2013curriculum, it is used in research, so researchers will share it and provide remediation solutions.Evaluation of learning has two dimensions, namely the evaluation of the learning process andevaluation of learning outcomes. Evaluation of the learning process is an evaluation system that needs tobe done by the teacher to determine the quality of learning. this activity is referred to as a reflection of thelearning process with this activity the teacher can find the advantages and disadvantages of the learningprocess that has been done. Evaluation of the learning process is a process to determine the value,services or benefits of learning activities through assessment and measurement activities. Making learningevaluations includes consideration of results, services, learning processes, and program benefits (Dimyatiand Mudjiono, 2006: 221). Evaluation of learning outcomes emphasizes the information to what extentthe results of the evaluation achieved by students in accordance with the stated goals. Thus, evaluation oflearning outcomes sets the good and bad results of learning activities.Researchers in determining the results of evaluation in learning multiliteration language andliterature divide it into three domains that each of them has its own evaluation method. The 2013curriculum system requires teachers that every basic competency can be evaluated so that students willachieve completeness in every competency. A separate evaluation system has an impact on the instructoras, the instructor must combine the way of learning, the teacher seeks material that matches thecombination of three competencies. Multiliteration evaluation allows the teacher to work hard to findreading material and learning models that can exclude the three competencies. Reading and writing haveseparate assessment criteria.